Sprayable ultra-high performance concrete for alpine regions and preparation and use methods thereof
By using the use of activated glass fiber and microcrystalline cellulose in high -performance concrete in high -cold regions, the problem of incomplete and insufficient water resistance in high -cold regions in high -cold regions and insufficient water resistance are solved. Essence
Patent Information
- Application Number
- CN202411509135.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-28
AI Technical Summary
When used in high-altitude areas, the existing spray concrete is unevenly dispersed during spraying due to unreasonable ratios, serious waste of materials, poor compressive strength and toughness, which cannot meet the requirements of water permeability.
The quality ratio of premixing and activating glass fiber is high-cold and high-performance concrete in high-cold areas with a mass ratio of 220-300: 6-12. The raw materials include cement, silica gray, coarse sand, fine sand, ultra-fine composite powder, water reducing water reducing water reduction Agent, choric agent, microcrystalline cellulose, methacryal methampite, nitrate ammonium, ethylamine, acrylic methyl ester, steel fiber, gallel oxide and water. By activating the mixing of glass fibers and premixing, it improves the adhesion and filling of the slurry, and enhances the water -resistant permeability through the branches of the branches of microcrystalline cellulose and the two -dimensional plane of the oxide graphene.
The problem of uneven scattered spraying slurry is solved, and the early intensity and water resistance of concrete are improved. It is suitable for construction in high -cold areas. The process is simple, shortening the construction period and improving economic benefits.
Smart Images

Figure CN119349954A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ultra-high performance concrete, and in particular to ultra-high performance concrete that can be sprayed in high-cold areas and a preparation method and use method thereof. Background Art
[0002] my country's infrastructure is developing rapidly. With the complexity of structural stress and harsh environmental conditions, conventional ordinary concrete has been unable to meet the high strength requirements of the structure. Ultra-high performance concrete has good application prospects in national defense engineering, marine engineering, nuclear industry, special security and protection engineering, and municipal engineering due to its excellent mechanical properties and durability, especially its anti-bending, low water absorption, high surface density, and stain resistance.
[0003] Tests have proven that the flexural strength of ultra-high performance concrete is twice that of ordinary C50 concrete, shrinkage is reduced by 50%, and it remains intact after 700 freeze-thaw cycles. Given the many advantages of ultra-high performance concrete, the application scenarios of this technology are becoming more and more extensive.
[0004] As architectural shapes become increasingly complex, direct pouring is difficult to achieve. Therefore, there is an urgent need to develop a concrete material system that can be sprayed. When my country's existing sprayed concrete is used in high-altitude cold areas, due to unreasonable proportions, the slurry is unevenly dispersed during spraying, resulting in a large amount of material waste; at the same time, the ultra-high performance sprayable concrete has the defects of poor compressive strength, poor toughness, and water permeability resistance that cannot meet the requirements. Summary of the invention
[0005] The purpose of the present invention is to solve the shortcomings of the prior art and to propose an ultra-high performance concrete that can be sprayed in high-cold areas and a preparation and use method thereof.
[0006] The invention discloses an ultra-high performance concrete which can be sprayed in high-cold areas. The raw materials of the ultra-high performance concrete include: a premix and activated glass fiber. The mass ratio of the premix to the activated glass fiber is 220-300:6-12.
[0007] The raw materials of the premix include, by mass, 70-80 parts of cement, 10-20 parts of silica fume, 5-15 parts of fly ash, 70-75 parts of coarse sand, 33-39 parts of fine sand, 10-15 parts of ultrafine composite powder, 4-6 parts of water reducer, 4-8 parts of accelerator, 5-10 parts of microcrystalline cellulose, 1-2 parts of methyl methacrylate, 0.01-0.1 parts of ammonium cerium nitrate, 1-2 parts of ethylenediamine, 1-2 parts of methyl acrylate, 3-7 parts of steel fiber, 1-2 parts of graphene oxide, and 13-17 parts of water.
[0008] The activated glass fiber is obtained by treating the glass fiber with alkali solution and then adding the siloxane into an ethanol aqueous solution and heating the solution.
[0009] Preferably, the cement is PO42.5 Portland cement.
[0010] Preferably, the coarse sand is 16-26 mesh machine-made sand, the fine sand is 26-40 mesh quartz sand, and the ultrafine composite powder is 40-80 mesh.
[0011] Preferably, the ultrafine composite powder is fluorite waste sand and / or copper slag.
[0012] Preferably, the activated glass fiber is prepared by the following specific operation: adding the glass fiber to a sodium hydroxide aqueous solution for ultrasonic treatment for 5-15 minutes, filtering, washing, vacuum drying, adding aminopropyltriethoxysilane to an ethanol aqueous solution, stirring at 80-90°C for 1-2 hours, filtering, washing, and vacuum drying.
[0013] Preferably, the mass ratio of glass fiber to aminopropyltriethoxysilane is 5-10:1-2.
[0014] Preferably, the concentration of the sodium hydroxide aqueous solution is 0.5-1.2 mol / L, and the mass fraction of the ethanol aqueous solution is 40-60%.
[0015] The method for preparing the ultra-high performance concrete that can be sprayed in high-cold areas comprises the following steps:
[0016] S1. Mix cement, silica fume, coarse sand, fine sand, ultrafine composite powder, water reducing agent and accelerating setting agent to obtain cementitious material;
[0017] S2, adding microcrystalline cellulose to methanol and stirring evenly, adding methyl methacrylate under nitrogen protection and stirring evenly, adding cerium ammonium nitrate, stirring at 30-50°C for 1-2h, adding ethylenediamine, stirring at 50-60°C for 5-15h, adding methyl acrylate and stirring for 10-20h, cooling to room temperature, adding water and centrifuging, washing, and vacuum drying to obtain activated cellulose;
[0018] S3, adding steel fiber, graphene oxide, activated cellulose and water to the gelling material and mixing them evenly to obtain a premix; mixing the premix with the activated glass fiber and spraying.
[0019] The method for using ultra-high performance concrete that can be sprayed in the above-mentioned high-altitude cold areas is to add the premix to the mortar sprayer for spraying construction, and the activated glass fiber is mixed with the premix at the nozzle of the mortar sprayer and sprayed.
[0020] Preferably, the mortar spraying machine operating parameters are as follows: delivery pressure is 2.5-4.2MPa, delivery flow rate is 1-3m 3 / min, the spraying distance is 1-1.6m, and the spraying thickness is controlled at 5-15mm per layer.
[0021] Beneficial effects:
[0022] 1. The present invention adopts activated cellulose to enhance the anti-sagging performance of mortar, and cooperates with activated glass fiber. The two are bonded by hydrogen bonds to link concrete cement with ultrafine composite powder, silica fume, fine sand and coarse sand, thereby improving the cohesiveness and filling property of the slurry and solving the problem of uneven dispersion when spraying the slurry.
[0023] 2. The present invention grafts dendritic macromolecules on the surface of microcrystalline cellulose to make the product surface rich in amino groups. With the action of activated glass fiber, it is added into the system step by step, so that the ultra-high performance concrete has good working performance, which can not only improve its early hydration reaction, and greatly improve the early strength compared with ordinary concrete, but also has good water permeability resistance in conjunction with the action of graphene oxide, and the setting time is adjustable. The two-dimensional plane of graphene oxide has a large number of functionalized binding sites, which increase the stability of the system in conjunction with activated cellulose, and can form intermolecular hydrogen bonds with water molecules, inhibit the crystallization of water molecules, and effectively lower the freezing point, which is particularly suitable for use in high-altitude cold areas.
[0024] 3. The present invention effectively avoids layered spraying, and the surface layer in contact with the mold does not expose fibers, further improving production efficiency. It can be sprayed for construction, has good fluidity and thixotropy after spraying, does not sag, and is suitable for construction with a variety of spraying equipment, and has broad application prospects.
[0025] 4. The preparation process of the present invention is simple, which ensures the smooth construction of shotcrete in a low temperature environment, effectively shortens the construction period, improves social and economic benefits, and is suitable for large-scale promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The figure is a comparison chart of the fluidity and 28d flexural strength of the concrete obtained in Example 5 and Comparative Examples 1-2.
[0027] Figure 2 The graph is a graph showing the compressive strength of the concrete obtained in Example 5 and Comparative Examples 1-2 versus curing time. DETAILED DESCRIPTION
[0028] The present invention will be further explained below in conjunction with specific embodiments.
[0029] The alkali-free liquid accelerator and polycarboxylate water reducer used below were purchased from Jiangsu Lai Te New Materials Co., Ltd. The accelerator model is SL15 and the polycarboxylate water reducer model is M171.
[0030] Example 1
[0031] The invention discloses an ultra-high performance concrete which can be sprayed in high-cold areas. The raw materials of the ultra-high performance concrete include: a premix and activated glass fiber. The mass ratio of the premix to the activated glass fiber is 227.41:6.
[0032] Among them, the raw materials of the premix include: 70kg PO42.5 silicate cement, 10kg silica fume, 5kg fly ash, 70kg 16-26 mesh machine-made sand, 33kg 26-40 mesh quartz sand, 10kg 40-80 mesh fluorite waste sand, 0.4kg polycarboxylic acid water reducer, 4kg alkali-free liquid accelerator, 5kg microcrystalline cellulose, 1kg methyl methacrylate, 0.01kg ammonium cerium nitrate, 1kg ethylenediamine, 1kg methyl acrylate, 3kg steel fiber, 1kg graphene oxide, and 13kg water.
[0033] The activated glass fiber was prepared by the following specific operation: 5 kg of glass fiber was added to 30 kg of 0.5 mol / L sodium hydroxide aqueous solution, ultrasonically treated for 5 min at an ultrasonic frequency of 5 kHz, filtered, washed, and vacuum dried, and 1 kg of aminopropyltriethoxysilane was added to 30 kg of 40% ethanol aqueous solution, stirred at 80°C for 1 h, filtered, washed, and vacuum dried.
[0034] The method for preparing the ultra-high performance concrete that can be sprayed in high-cold areas comprises the following steps:
[0035] S1. Add cement, silica fume, machine-made sand, quartz sand, fluorite waste sand, water reducer and accelerator into a mortar mixer and stir evenly to obtain a cementitious material;
[0036] S2, adding microcrystalline cellulose to 20 kg of methanol and stirring evenly, adding methyl methacrylate under nitrogen protection and stirring evenly, adding cerium ammonium nitrate, stirring at 30 ° C for 1 hour, adding ethylenediamine, stirring at 50 ° C for 5 hours, adding methyl acrylate and stirring for 10 hours, cooling to room temperature, adding 50 kg of water, centrifuging, washing, and vacuum drying to obtain activated cellulose;
[0037] S3, adding steel fiber, graphene oxide, activated cellulose and water to the gelling material and mixing them evenly to obtain a premix; mixing the premix with the activated glass fiber and spraying.
[0038] The method for using ultra-high performance concrete that can be sprayed in the above-mentioned high-altitude cold areas is to add the premix to the mortar sprayer for spraying construction; and the activated glass fiber is mixed with the premix at the nozzle of the mortar sprayer and sprayed.
[0039] Among them, the working parameters of the mortar spraying machine are as follows: the delivery pressure is 2.5MPa, the delivery flow rate is 1m 3 / min, the spraying distance is 1m, and the spraying thickness is controlled at 5mm per layer.
[0040] Example 2
[0041] The invention discloses an ultra-high performance concrete which can be sprayed in high-cold areas. The raw materials of the ultra-high performance concrete include: a premix and activated glass fiber, and the mass ratio of the premix to the activated glass fiber is 294.9:12.
[0042] Among them, the raw materials of the premix include: 80kg of PO42.5 silicate cement, 20kg of silica fume, 15kg of fly ash, 75kg of 16-26 mesh machine-made sand, 39kg of 26-40 mesh quartz sand, 15kg of 40-80 mesh copper slag, 0.8kg of polycarboxylic acid water reducer, 8kg of alkali-free liquid accelerator, 10kg of microcrystalline cellulose, 2kg of methyl methacrylate, 0.1kg of ammonium cerium nitrate, 2kg of ethylenediamine, 2kg of methyl acrylate, 7kg of steel fiber, 2kg of graphene oxide, and 17kg of water.
[0043] The activated glass fiber was prepared by the following specific operation: 10 kg of glass fiber was added to 50 kg of 1.2 mol / L sodium hydroxide aqueous solution, ultrasonically treated for 15 min at an ultrasonic frequency of 10 kHz, filtered, washed, and vacuum dried, and 2 kg of aminopropyltriethoxysilane was added to 50 kg of 60% ethanol aqueous solution, stirred at 90°C for 2 h, filtered, washed, and vacuum dried.
[0044] The method for preparing the ultra-high performance concrete that can be sprayed in high-cold areas comprises the following steps:
[0045] S1. Add cement, silica fume, machine-made sand, quartz sand, copper slag, water reducing agent and accelerating setting agent into a mortar mixer and stir evenly to obtain a cementitious material;
[0046] S2, adding microcrystalline cellulose to 40 kg of methanol and stirring evenly, adding methyl methacrylate under nitrogen protection and stirring evenly, adding cerium ammonium nitrate, stirring at a temperature of 50 ° C for 2 hours, adding ethylenediamine, stirring at a temperature of 60 ° C for 15 hours, adding methyl acrylate and stirring for 20 hours, cooling to room temperature, adding 100 kg of water, centrifuging, washing, and vacuum drying to obtain activated cellulose;
[0047] S3, adding steel fiber, graphene oxide, activated cellulose and water to the gelling material and mixing them evenly to obtain a premix; mixing the premix with the activated glass fiber and spraying.
[0048] The method for using ultra-high performance concrete that can be sprayed in the above-mentioned high-altitude cold areas is to add the premix to the mortar sprayer for spraying construction; and the activated glass fiber is mixed with the premix at the nozzle of the mortar sprayer and sprayed.
[0049] Among them, the working parameters of the mortar spraying machine are as follows: the delivery pressure is 4.2MPa, the delivery flow rate is 3m 3 / min, the spraying distance is 1.6m, and the spraying thickness is controlled at 15mm per layer.
[0050] Example 3
[0051] The invention discloses an ultra-high performance concrete which can be sprayed in high-cold areas. The raw materials of the ultra-high performance concrete include: a premix and activated glass fiber. The mass ratio of the premix to the activated glass fiber is 261.63:7.8.
[0052] Among them, the raw materials of the premix include: PO42.5 silicate cement 73kg, silica fume 18kg, fly ash 8kg, 16-26 mesh machine-made sand 73kg, 26-40 mesh quartz sand 35kg, 40-80 mesh fluorite waste sand 10kg, 40-80 mesh copper slag 3kg, polycarboxylic acid water reducer 0.5kg, alkali-free liquid accelerator 7kg, microcrystalline cellulose 6kg, methyl methacrylate 1.7kg, cerium ammonium nitrate 0.03kg, ethylenediamine 1.8kg, methyl acrylate 1.3kg, steel fiber 6kg, graphene oxide 1.3kg, and water 16kg.
[0053] The activated glass fiber was prepared by the following specific operation: 6 kg of glass fiber was added to 45 kg of 0.6 mol / L sodium hydroxide aqueous solution, ultrasonically treated for 12 min at an ultrasonic frequency of 7 kHz, filtered, washed, and vacuum dried, and 1.8 kg of aminopropyltriethoxysilane was added to 35 kg of 55% ethanol aqueous solution, stirred at 82°C for 100 min, filtered, washed, and vacuum dried.
[0054] The method for preparing the ultra-high performance concrete that can be sprayed in high-cold areas comprises the following steps:
[0055] S1. Add cement, silica fume, machine-made sand, quartz sand, fluorite waste sand, copper slag, water reducer and accelerator into a mortar mixer and stir evenly to obtain a cementitious material;
[0056] S2, adding microcrystalline cellulose to 25 kg of methanol and stirring evenly, adding methyl methacrylate under nitrogen protection and stirring evenly, adding cerium ammonium nitrate, stirring at a temperature of 45 ° C for 80 minutes, adding ethylenediamine, stirring at a temperature of 58 ° C for 8 hours, adding methyl acrylate and stirring for 18 hours, cooling to room temperature, adding 60 kg of water, centrifuging, washing, and vacuum drying to obtain activated cellulose;
[0057] S3, adding steel fiber, graphene oxide, activated cellulose and water to the gelling material and mixing them evenly to obtain a premix; mixing the premix with the activated glass fiber and spraying.
[0058] The method for using ultra-high performance concrete that can be sprayed in the above-mentioned high-altitude cold areas is to add the premix to the mortar sprayer for spraying construction; and the activated glass fiber is mixed with the premix at the nozzle of the mortar sprayer and sprayed.
[0059] Among them, the working parameters of the mortar spraying machine are as follows: the delivery pressure is 4MPa, the delivery flow rate is 2.5m 3 / min, the spraying distance is 1.4m, and the spraying thickness is controlled at 12mm per layer.
[0060] Example 4
[0061] The invention discloses an ultra-high performance concrete which can be sprayed in high-cold areas. The raw materials of the ultra-high performance concrete include: a premix and activated glass fiber. The mass ratio of the premix to the activated glass fiber is 257.67:9.2.
[0062] Among them, the raw materials of the premix include: 77kg PO42.5 silicate cement, 12kg silica ash, 12kg fly ash, 71kg 16-26 mesh machine-made sand, 37kg 26-40 mesh quartz sand, 2kg 40-80 mesh fluorite waste sand, 9kg 40-80 mesh copper slag, 0.7kg polycarboxylic acid water reducer, 5kg alkali-free liquid accelerator, 8kg microcrystalline cellulose, 1.3kg methyl methacrylate, 0.07kg ammonium cerium nitrate, 1.2kg ethylenediamine, 1.7kg methyl acrylate, 4kg steel fiber, 1.7kg graphene oxide, and 14kg water.
[0063] The activated glass fiber was prepared by the following specific operation: 8 kg of glass fiber was added to 35 kg of 1 mol / L sodium hydroxide aqueous solution, ultrasonically treated for 8 min at an ultrasonic frequency of 9 kHz, filtered, washed, and vacuum dried, and 1.2 kg of aminopropyltriethoxysilane was added to 45 kg of 45% ethanol aqueous solution, stirred at 88°C for 80 min, filtered, washed, and vacuum dried.
[0064] The method for preparing the ultra-high performance concrete that can be sprayed in high-cold areas comprises the following steps:
[0065] S1. Add cement, silica fume, machine-made sand, quartz sand, fluorite waste sand, copper slag, water reducer and accelerator into a mortar mixer and stir evenly to obtain a cementitious material;
[0066] S2, adding microcrystalline cellulose to 35 kg of methanol and stirring evenly, adding methyl methacrylate under nitrogen protection and stirring evenly, adding cerium ammonium nitrate, stirring at 35 ° C for 100 min, adding ethylenediamine, stirring at 52 ° C for 12 h, adding methyl acrylate and stirring for 12 h, cooling to room temperature, adding 90 kg of water, centrifuging, washing, and vacuum drying to obtain activated cellulose;
[0067] S3, adding steel fiber, graphene oxide, activated cellulose and water to the gelling material and mixing them evenly to obtain a premix; mixing the premix with the activated glass fiber and spraying.
[0068] The method for using ultra-high performance concrete that can be sprayed in the above-mentioned high-altitude cold areas is to add the premix to the mortar sprayer for spraying construction; and the activated glass fiber is mixed with the premix at the nozzle of the mortar sprayer and sprayed.
[0069] Among them, the working parameters of the mortar spraying machine are as follows: the delivery pressure is 2.8MPa, the delivery flow rate is 1.5m 3 / min, the spraying distance is 1.2m, and the spraying thickness is controlled at 8mm per layer.
[0070] Example 5
[0071] An ultra-high performance concrete that can be sprayed in high-cold areas, the raw materials of which include: premix and activated glass fiber, the mass ratio of the premix to the activated glass fiber is 259.65:8.5.
[0072] Among them, the raw materials of the premix include: 75kg PO42.5 silicate cement, 15kg silica ash, 10kg fly ash, 72kg 16-26 mesh machine-made sand, 36kg 26-40 mesh quartz sand, 6kg 40-80 mesh fluorite waste sand, 6kg 40-80 mesh copper slag, 0.6kg polycarboxylic acid water reducer, 6kg alkali-free liquid accelerator, 7kg microcrystalline cellulose, 1.5kg methyl methacrylate, 0.05kg ammonium cerium nitrate, 1.5kg ethylenediamine, 1.5kg methyl acrylate, 5kg steel fiber, 1.5kg graphene oxide, and 15kg water.
[0073] The activated glass fiber was prepared by the following specific operation: 7 kg of glass fiber was added to 40 kg of 0.8 mol / L sodium hydroxide aqueous solution, ultrasonically treated for 10 min at an ultrasonic frequency of 8 kHz, filtered, washed, and vacuum dried, and 1.5 kg of aminopropyltriethoxysilane was added to 40 kg of 50% ethanol aqueous solution, stirred at 85°C for 90 min, filtered, washed, and vacuum dried.
[0074] The method for preparing the ultra-high performance concrete that can be sprayed in high-cold areas comprises the following steps:
[0075] S1. Add cement, silica fume, machine-made sand, quartz sand, fluorite waste sand, copper slag, water reducer and accelerator into a mortar mixer and stir evenly to obtain a cementitious material;
[0076] S2, adding microcrystalline cellulose to 30 kg of methanol and stirring evenly, adding methyl methacrylate under nitrogen protection and stirring evenly, adding cerium ammonium nitrate, stirring at a temperature of 40 ° C for 90 minutes, adding ethylenediamine, stirring at a temperature of 55 ° C for 10 hours, adding methyl acrylate and stirring for 15 hours, cooling to room temperature, adding 75 kg of water, centrifuging, washing, and vacuum drying to obtain activated cellulose;
[0077] S3, adding steel fiber, graphene oxide, activated cellulose and water to the gelling material and mixing them evenly to obtain a premix; mixing the premix with the activated glass fiber and spraying.
[0078] The method for using ultra-high performance concrete that can be sprayed in the above-mentioned high-altitude cold areas is to add the premix to the mortar sprayer for spraying construction; and the activated glass fiber is mixed with the premix at the nozzle of the mortar sprayer and sprayed.
[0079] Among them, the working parameters of the mortar spraying machine are as follows: the delivery pressure is 3.2MPa, the delivery flow rate is 2m 3 / min, the spraying distance is 1.3m, and the spraying thickness is controlled at 10mm per layer.
[0080] Comparative Example 1
[0081] An ultra-high performance concrete that can be sprayed in high-cold areas, the raw materials of which include: premix and glass fiber, and the mass ratio of the premix to the glass fiber is 259.65:8.5.
[0082] Among them, the raw materials of the premix include: 75kg PO42.5 silicate cement, 15kg silica ash, 10kg fly ash, 72kg 16-26 mesh machine-made sand, 36kg 26-40 mesh quartz sand, 6kg 40-80 mesh fluorite waste sand, 6kg 40-80 mesh copper slag, 0.6kg polycarboxylic acid water reducer, 6kg alkali-free liquid accelerator, 7kg microcrystalline cellulose, 1.5kg methyl methacrylate, 0.05kg ammonium cerium nitrate, 1.5kg ethylenediamine, 1.5kg methyl acrylate, 5kg steel fiber, 1.5kg graphene oxide, and 15kg water.
[0083] The method for preparing the ultra-high performance concrete that can be sprayed in high-cold areas comprises the following steps:
[0084] S1. Add cement, silica fume, machine-made sand, quartz sand, fluorite waste sand, copper slag, water reducer and accelerator into a mortar mixer and stir evenly to obtain a cementitious material;
[0085] S2, adding microcrystalline cellulose to 30 kg of methanol and stirring evenly, adding methyl methacrylate under nitrogen protection and stirring evenly, adding cerium ammonium nitrate, stirring at a temperature of 40 ° C for 90 minutes, adding ethylenediamine, stirring at a temperature of 55 ° C for 10 hours, adding methyl acrylate and stirring for 15 hours, cooling to room temperature, adding 75 kg of water, centrifuging, washing, and vacuum drying to obtain activated cellulose;
[0086] S3, adding steel fiber, graphene oxide, activated cellulose and water to the agglomerate and mixing them evenly to obtain a premix; mixing the premix with glass fiber and spraying.
[0087] Comparative Example 2
[0088] An ultra-high performance concrete that can be sprayed in high-cold areas, the raw materials of which include: premix and activated glass fiber, the mass ratio of the premix to the activated glass fiber is 259.65:8.5.
[0089] Among them, the raw materials of the premix include: 75kg PO42.5 silicate cement, 15kg silica ash, 10kg fly ash, 72kg 16-26 mesh machine-made sand, 36kg 26-40 mesh quartz sand, 6kg 40-80 mesh fluorite waste sand, 6kg 40-80 mesh copper slag, 0.6kg polycarboxylic acid water reducer, 6kg alkali-free liquid accelerator, 7kg microcrystalline cellulose, 1.5kg methyl methacrylate, 0.05kg ammonium cerium nitrate, 1.5kg ethylenediamine, 1.5kg methyl acrylate, 5kg steel fiber, 1.5kg graphene oxide, and 15kg water.
[0090] The activated glass fiber was prepared by the following specific operation: 7 kg of glass fiber was added to 40 kg of 0.8 mol / L sodium hydroxide aqueous solution, ultrasonically treated for 10 min at an ultrasonic frequency of 8 kHz, filtered, washed, and vacuum dried, and 1.5 kg of aminopropyltriethoxysilane was added to 40 kg of 50% ethanol aqueous solution, stirred at 85°C for 90 min, filtered, washed, and vacuum dried.
[0091] The method for preparing the ultra-high performance concrete that can be sprayed in high-cold areas comprises the following steps:
[0092] S1. Add cement, silica fume, machine-made sand, quartz sand, fluorite waste sand, copper slag, water reducer and accelerator into a mortar mixer and stir evenly to obtain a cementitious material;
[0093] S2, mixing microcrystalline cellulose, methyl methacrylate, cerium ammonium nitrate, ethylenediamine, and methyl acrylate to obtain pretreated microcrystalline cellulose;
[0094] S3, adding steel fiber, graphene oxide, pretreated microcrystalline cellulose and water to the gelling material and mixing them evenly to obtain a premix; mixing the premix with activated glass fiber and spraying.
[0095] With reference to GB / T 2419-2005 "Method for determination of fluidity of cement mortar", a cement mortar fluidity tester was used to determine the fluidity of the mortars obtained in Example 5 and Comparative Examples 1-2.
[0096] With reference to GB / T 17671-2021 "Test Method for Strength of Cement Mortar (ISO Method)", the mortar obtained in Example 5 and Comparative Examples 1-2 was cast into 40mm×40mm×160mm specimens, and then the specimens were cured in a concrete high-temperature steam rapid curing box, with the curing temperature set to 50°C and the curing time set to 28d. After the curing was completed, the flexural strength test was first carried out, and the compression test was carried out on the broken prism. The compression surface was the two side surfaces of the specimen when it was formed, with an area of 40mm×40mm.
[0097] The flexural strength was tested on a SANS YAW-100 compression-flexure testing machine. The side of the specimen was placed on the fixture, and the loading rate of the testing machine was 50±10N / s. The side of the broken specimen end was then placed on the fixture, and the loading rate was set to 2400±200N / s, with uniform loading until the specimen was destroyed.
[0098] like Figure 1 and Figure 2 As shown, the fluidity and 28d flexural strength of the concrete obtained in Example 5 are the highest, which are better than those of Comparative Examples 1-2 (P < 0.05); and the early strength performance of the concrete obtained in Example 5 is the best, and the 1d compressive strength reaches 94.84% of the 28d compressive strength. At the same time, the compressive strength of the concrete obtained in Example 5 is always higher than that of Comparative Examples 1-2 (P < 0.05).
[0099] The applicant believes that this is because the present invention grafts dendritic macromolecules on the surface of microcrystalline cellulose, so that the surface of the product contains rich amino groups, which cooperates with the effect of activated glass fiber and is added to the system step by step, so that the ultra-high performance concrete has good working performance, can improve its early hydration reaction, and the early strength is greatly improved compared with ordinary concrete.
[0100] The concrete obtained in Example 5 and Comparative Examples 1-2 after curing for 28 days was tested for impermeability according to GB 50164-2011 "Concrete Quality Control Standard". The concrete obtained in Example 5 had an impermeability of P40, the concrete obtained in Comparative Example 1 had an impermeability of P27, and the concrete obtained in Comparative Example 2 had an impermeability of P19.
[0101] The applicant believes that this is because the present invention grafts dendritic macromolecules on the surface of microcrystalline cellulose, so that the surface of the product contains rich amino groups, and cooperates with the action of activated glass fiber, and is added to the system step by step, and cooperates with the action of graphene oxide to have good water permeability resistance. The two-dimensional plane of graphene oxide has a large number of functionalized binding sites, which cooperates with activated cellulose to increase the stability of the system, and can form intermolecular hydrogen bonds with water molecules, inhibiting the crystallization of water molecules and effectively lowering the freezing point, which is particularly suitable for use in high-altitude cold areas.
[0102] The mortars obtained in Example 5 and Comparative Examples 1-2 were used for vertical wall spraying according to the method used in Example 5. It was found that the spraying surface of the mortar obtained in Example 5 was uniform, while the spraying effect of Comparative Example 1 was not ideal, with occasional blockage and pulse "blasting" phenomena; although Comparative Example 2 could be sprayed, it was unevenly dispersed during spraying, and fiber clusters were visible on the spraying surface.
[0103] The applicant believes that this is because the present invention uses activated cellulose to enhance the anti-sagging performance of the mortar, combined with activated glass fiber, the two are bonded through hydrogen bonds, and the concrete cement is linked with the ultrafine composite powder, silica fume, fine sand and coarse sand, thereby improving the cohesiveness and filling properties of the slurry and solving the problem of uneven dispersion during spraying of the spray slurry.
[0104] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. An ultra-high performance concrete that can be sprayed in cold regions, characterized in that: The raw materials include: premix and activated glass fiber, the mass ratio of the premix to the activated glass fiber is 220-300:6-12; The raw materials of the premix include, by mass: 70-80 parts of cement, 10-20 parts of silica fume, 5-15 parts of fly ash, 70-75 parts of coarse sand, 33-39 parts of fine sand, 10-15 parts of ultrafine composite powder, 4-6 parts of water reducer, 4-8 parts of accelerator, 5-10 parts of microcrystalline cellulose, 1-2 parts of methyl methacrylate, 0.01-0.1 parts of ammonium cerium nitrate, 1-2 parts of ethylenediamine, 1-2 parts of methyl acrylate, 3-7 parts of steel fiber, 1-2 parts of graphene oxide, and 13-17 parts of water; The activated glass fiber is obtained by treating the glass fiber with alkali solution and then adding the siloxane into an ethanol aqueous solution and heating the solution.
2. The ultra-high performance concrete sprayable in high-cold regions according to claim 1 is characterized in that: The cement is PO42.5 silicate cement.
3. The ultra-high performance concrete sprayable in high-cold regions according to claim 1 is characterized in that: The coarse sand is 16-26 mesh machine-made sand, the fine sand is 26-40 mesh quartz sand, and the ultrafine composite powder is 40-80 mesh.
4. The ultra-high performance concrete sprayable in high-cold regions according to claim 1 is characterized in that: The ultrafine composite powder is fluorite waste sand and / or copper slag.
5. The ultra-high performance concrete sprayable in high-cold regions according to claim 1 is characterized in that: The activated glass fiber is prepared by the following specific operation: adding the glass fiber to a sodium hydroxide aqueous solution for ultrasonic treatment for 5-15 minutes, filtering, washing, vacuum drying, adding aminopropyltriethoxysilane to an ethanol aqueous solution, stirring at 80-90° C. for 1-2 hours, filtering, washing, and vacuum drying.
6. The ultra-high performance concrete sprayable in high-cold regions according to claim 5, characterized in that: The mass ratio of glass fiber to aminopropyltriethoxysilane is 5-10:1-2.
7. The ultra-high performance concrete sprayable in high-cold regions according to claim 5, characterized in that: The concentration of the sodium hydroxide aqueous solution is 0.5-1.2 mol / L, and the mass fraction of the ethanol aqueous solution is 40-60%.
8. A method for preparing ultra-high performance concrete sprayable in high-cold regions as claimed in any one of claims 1 to 7, characterized in that: The steps include: S1. Mix cement, silica fume, coarse sand, fine sand, ultrafine composite powder, water reducing agent and accelerating setting agent to obtain cementitious material; S2, adding microcrystalline cellulose to methanol and stirring evenly, adding methyl methacrylate under nitrogen protection and stirring evenly, adding cerium ammonium nitrate, stirring at 30-50°C for 1-2h, adding ethylenediamine, stirring at 50-60°C for 5-15h, adding methyl acrylate and stirring for 10-20h, cooling to room temperature, adding water and centrifuging, washing, and vacuum drying to obtain activated cellulose; S3, adding steel fiber, graphene oxide, activated cellulose and water to the gelling material and mixing them evenly to obtain a premix; mixing the premix with the activated glass fiber and spraying.
9. A method for using the ultra-high performance concrete sprayable in high-cold regions as claimed in any one of claims 1 to 7, characterized in that: The premix is added into a mortar sprayer for spraying construction, and the activated glass fiber is mixed with the premix at the nozzle of the mortar sprayer for spraying.
10. The method for using the ultra-high performance concrete sprayable in high-cold regions according to claim 9, characterized in that: The working parameters of the mortar spraying machine are as follows: the delivery pressure is 2.5-4.2MPa, the delivery flow rate is 1-3m 3 / min, the spraying distance is 1-1.6m, and the spraying thickness is controlled at 5-15mm per layer.
Citation Information
Patent Citations
Ultra-high performance concrete with high breaking strength and preparation method thereof
CN113480257A
Anti-freezing accelerator, preparation method thereof and sprayed concrete
CN115368051A
Spraying adjustable setting ultra-high performance concrete
CN117865598A
Lake bottom sludge treatment agent and preparation method thereof
CN118812212A
Surfactant-free emulsions of cellulose nanocrystal-polymer nanocomposite and method to prepare the same
WO2021113960A1